MnO2 doped carbon nanosheets prepared from coal tar pitch for advanced asymmetric supercapacitor. (10th September 2020) - Yang, Yikai; Niu, Hao; Qin, Fangfang; Guo, Zhongya; Wang, Jiashi; Ni, Guosong; Zuo, Pingping; Qu, Shijie; Shen, Wenzhong
Abstract: As promising precursor of functional carbon materials, coal tar pitch was selected as a precursor to prepare porous carbon nanosheets (PCN). Then MnO2 was incorporated into porous carbon nanosheets to form MnO2 @PCN by hydrothermal treatment. Both PCN and MnO2 @PCN showed high specific surface areas (1605 m 2 /g and 836 m 2 /g) and nanosheets structures with the thickness of 30 ± 5 nm and 60 ± 10 nm, respectively. When PCN and MnO2 @PCN were used as electrode materials of supercapacitors, PCN displayed ideal electrical double layer capacitive characteristics and excellent rate performance, but a narrow operating voltage window and relatively low specific capacitance (225 F/g at 0.5 A/g) in 1 M Na2 SO4 aqueous; while the MnO2 @PCN possessed high-rate performance, low charge transport resistance, extended the operating voltage window (−0.2 V–0.8 V) and improved the specific capacitance (377 F/g at 0.5 A/g). Furthermore, the asymmetric supercapacitors fabricated with MnO2 @PCN as cathode and PCN as anode also exhibited high specific capacitance (87.8 F/g at 0.5 A/g), superior energy density (31.13 Wh/kg at 193.6 W/kg) and good cyclic ability (88.3% after 5000 cycles). This work provided an alternative preparation of high-performance porous carbon composite for resource utilization of coal tar pitch. Graphical abstract: Image 1